Hubungan Antara Narasi Film dengan Pengetahuan Penonton Mengenai Isu Kesehatan Mental - Audry Putri Nurdiawati; Firmansyash (UNISBA Press, 2023)
Abstract. Film is a mass communication medium that can meet the public's need for information and entertainment. This is what makes films have a special appeal for the public. Even during a pandemic, when almost all sectors, especially the economy, are experiencing a decline, films have their own way of attracting their fans. Like the film